A victimological study among Coloureds in the Cape Peninsula - Strijdom, Hendrik Gert (Rhodes University, Faculty of Humanities, Department of Sociology, 1983)
From Introduction: Criminology developed as a reaction to the various revolutions that were occurring in the European countries during the eighteenth and nineteenth centuries. In response to the turmoil and disorder of Western society criminologists attempted to discover the natural laws of society hoping to establish a stable social order. Crime was regarded as something that disturbed society and, therefore, had to be controlled or prevented. According to Quinney and Wildeman (1977) the development of criminology can be viewed as an ongoing attempt to explain crime in terms of established social order. They state that in the history of criminology there is, however, a lack of a clear accumulative theoretical growth and continue as follows: "No line of theoretical development can be found that leads to a well-developed body of knowledge. The study of crime is characterized by a number of divergent theoretical perspectives that exist in relative isolation from one another" (p. 38). Quinney and Wildeman (1977) distinguish five theoretical perspectives in the development of criminology namely: (I) early and classical criminological thought, (2) nineteenth-century sociological criminology, (3) nineteenth-century biological criminology, (4) twentieth-century eclectic criminology, and (5) twentieth-century sociological criminology.
Keywords: Victims of crimes -- South Africa -- Western Cape; Colored people (South Africa) -- Social conditions